2017
DOI: 10.1017/jie.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Outside the Circle: Reflections on Theory and Methods for School-Based Garden Research

Abstract: School-based gardens (SBGs) are contributing to improvements in many areas of education, including nutrition, health, connectedness and engagement of students. While considerable research has been conducted in other parts of the world, research in Australia provides limited understanding of the impact of SBGs. The aim of this paper is to give a reflective viewpoint on the impact of SBGs in Australia from the perspective of an Aboriginal philosophical approach called Dadirri. The philosophy highlights an Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…As Fleer, (2019) found that play-way pedagogy in science is the best method to develop and understand science concepts. Many other researcher (Clague, Harrison, Stewart, & Atkinson, 2018;Rogers, Livstrom, Roiger, & Smith, 2019;Williams, Brule, Kelley, & Skinner, 2018) found that garden-based activities show promise for supporting students' engagement and learning in science classes and in fostering students' interest in pursuing science long-term impacts on basic scientific concepts to upgrade knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…As Fleer, (2019) found that play-way pedagogy in science is the best method to develop and understand science concepts. Many other researcher (Clague, Harrison, Stewart, & Atkinson, 2018;Rogers, Livstrom, Roiger, & Smith, 2019;Williams, Brule, Kelley, & Skinner, 2018) found that garden-based activities show promise for supporting students' engagement and learning in science classes and in fostering students' interest in pursuing science long-term impacts on basic scientific concepts to upgrade knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…To hear a voice requires a person to listen, to listen deeply. Deep listening is also referred to as dadirri (Clague et al, 2018). Dadirri derives from the Ngangikurungkurr language of the MalakMalak people of the Daly River region of the Northern Territory.…”
Section: Weaving a Basket: Kelly’s Theoretical Frameworkmentioning
confidence: 99%
“…And Bundjalung scholar and educator Leisa Clague and her colleagues note thatWhile Dadirri comes from Nauiyu Country, other language groups have equivalent words to describe a similar process, such as Gan’na from the Bundjalung people (North Coast, New South Wales) is to hear, listen, feel, think and understand. (Clague et al, 2018: 141)…”
Section: Listening Matters Toomentioning
confidence: 99%